Students' evidenced claims for development of abilities arising from linked reflection-on-action and reflection-for-action. Issue 2 (3rd March 2020) - Cowan, John
ABSTRACT: The development of graduate attributes through structured planning of linked reflective reviews of problem-based learning is evaluated. Data is obtained by summarising students' reflections-on-action in their evidence-based review claims and on their forward planning, based on immediate reflection-for-action.